2016
DOI: 10.1097/md.0000000000004056
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of freezing of gait with early Parkinson disease in Chinese patients

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
72
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(90 citation statements)
references
References 31 publications
16
72
1
1
Order By: Relevance
“…Our previous cross‐sectional study (Ou et al., ) has found that patients with onset in lower limbs were associated with the presence of FOG. In the current study, we verified that patients with onset in lower limbs were likely to develop FOG episodes, which is in accordance with the finding of another prospective study from China (Zhang et al., ). The pathophysiological mechanism of FOG episodes is poorly understood.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our previous cross‐sectional study (Ou et al., ) has found that patients with onset in lower limbs were associated with the presence of FOG. In the current study, we verified that patients with onset in lower limbs were likely to develop FOG episodes, which is in accordance with the finding of another prospective study from China (Zhang et al., ). The pathophysiological mechanism of FOG episodes is poorly understood.…”
Section: Discussionsupporting
confidence: 93%
“…In the current study, we found that patients with longer disease duration are more likely to develop FOG episodes. This is consistent with the findings of a previous prospective study (Giladi et al., ) and several cross‐sectional studies (Garcia‐Ruiz, del Val, Fernandez, & Herranz, ; Giladi et al., ; Macht et al., ), but is not consistent with the results from two other prospective studies (Forsaa et al., ; Zhang et al., ). Our study also found that higher disease severity is a risk factor for FOG.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…It has been shown that education level has a significant impact on the clinical presentation of symptoms in PD [63]. Health beliefs have also been related to cultural differences, and therefore might influence the perception of PD and individual symptoms.…”
Section: Discussionmentioning
confidence: 99%